2016
DOI: 10.1017/s0261444816000173
|View full text |Cite
|
Sign up to set email alerts
|

Language learning motivation through a small lens: A research agenda

Abstract: In this paper I propose an agenda for researching language learning motivation 'through a small lens', to counteract our tendency in the L2 motivation field to engage with language learning and teaching processes at a rather general level. I argue that by adopting a more sharply focused or contextualized angle of inquiry, we may be able to understand better how motivation connects with specific aspects of SLA or particular features of linguistic development. Keeping the empirical focus narrow may also lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 35 publications
4
91
0
1
Order By: Relevance
“…Supporting the theoretical claims of many L2 motivation scholars (Dörnyei, , ; Ushioda, ), our study is the first attempt to provide empirical evidence that having strongly internalized future‐self guides—Ideal L2 Self—could be a strong antecedent for successful L2 development. One reason for this could be that motivation is believed to help L2 learners foster their awareness, noticing, and understanding of input, especially when there is no input enhancement, as evidenced in L2 research (e.g., Takahashi, ) and in social psychology (e.g., Newsome, ).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Supporting the theoretical claims of many L2 motivation scholars (Dörnyei, , ; Ushioda, ), our study is the first attempt to provide empirical evidence that having strongly internalized future‐self guides—Ideal L2 Self—could be a strong antecedent for successful L2 development. One reason for this could be that motivation is believed to help L2 learners foster their awareness, noticing, and understanding of input, especially when there is no input enhancement, as evidenced in L2 research (e.g., Takahashi, ) and in social psychology (e.g., Newsome, ).…”
Section: Discussionsupporting
confidence: 78%
“…In response to the first research question concerning the interaction patterns between L2 learners’ motivation and emotion factors and their experience, our cross‐sectional and longitudinal analyses demonstrated that both Ideal L2 Self and Ought‐to L2 Self demonstrated small‐to‐medium correlations with various stages of the participants’ experience at preschool, junior high school, and high school ( r = .20–.30), indicating that motivation is closely aligned with L2 learners’ behaviors relating to studying, using, and practicing the target language throughout their EFL experience (Dörnyei, ; Ushioda, ). Interestingly, the degree of the participants’ positive feelings about their own EFL learning (Private Enjoyment) predicted the quantity/quality of their most recent experience (at both T1 and T2).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This may be particularly the case in relation to digital text production, the creation of online media offering opportunities for personal expression, creative thinking, and audience interaction (Blake, ). Responsive to the need to integrate varying theoretical frameworks in studying aspects of learner psychology (Mercer & Ryan, ), and heeding Ushioda's () call for L2 motivation research that is “grounded in specific contexts of practice” (p. 566), the purpose of this study is to develop a theoretical understanding of motivation that emerges in activities involving online media creation. Adopting a grounded theory approach (Charmaz, ) and viewing blogging as a participatory process (Ito et al., ), the research was guided by the question: How can we understand L2 motivation that arises when learners create online media?…”
Section: Purposementioning
confidence: 99%